The Functional Role of Historical Analogies in Russian and Ukrainian Presidential Discourses on the Special Military Operation - Vladimir O. Bekliamishev (RUDN Journal of Political Science)
The application of historical analogies in Russian and Ukrainian presidential discourses in the initial period of the special military operation (24.02-21.09.2022) is noteworthy. The purpose of the study was to identify their functional role. The results demonstrated that two ontologies of the conflict coexisted in the Russian presidential discourse. The dominant ontology, set by a parallel with the Great Patriotic War, assumed the collective West as an enemy, that uses Ukraine as a “foothold”. The second ontology, described through a parallel with the Russian Civil War, gave Ukraine greater subjectivity, assigning the collective West the role of a third party benefiting from the conflict. In turn, the repertoire of historical analogies in the Ukrainian presidential discourse was much broader, but most of the identified parallels were based on precedent situations from foreign history and were used to influence the perception of the Russian-Ukrainian conflict by the countries of the collective West. The noted imbalance was partly since unresolved structural conflicts between Soviet and nationalist narratives prevented Ukrainian elites from effectively using historical arguments in domestic political communication.